Speckle photography with different pupils in a multiple-exposure scheme (2000)
The use of different multiple-aperture pupils for recording each image in speckle photography is proposed -- The introduction of suitable spatial frequency carriers, by internally modulating imaged speckles, allows one to selectively isolate or combine the spectral content of different images into spatially separated regions in the Fourier plane -- Theoretical and experimental results extend the speckle photography technique to the depiction of several specklegrams of multiple uniform in-plane displacements -- In this case, because different pupils are considered for recording, the cross-correlation functions for the amplitudes and intensities in the image plane are calculated on the basis of the statistical properties of the object -- Also, the ensemble-average intensity in the Fourier plane is analytically derived, and fringe visibility is investigated. © 2000 Optical Society of America [S0740-3232(00)01701-4]OCIS codes: 120.0120, 120.3180, 120.3940, 120.6160